2021
DOI: 10.3390/ijms22168791
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Increases Macrophage Cholesterol Efflux through Regulation of ABCA1 and ABCG1 in Different Mechanisms

Abstract: Lipid dysregulation in diabetes mellitus escalates endothelial dysfunction, the initial event in the development and progression of diabetic atherosclerosis. In addition, lipid-laden macrophage accumulation in the arterial wall plays a significant role in the pathology of diabetes-associated atherosclerosis. Therefore, inhibition of endothelial dysfunction and enhancement of macrophage cholesterol efflux is the important antiatherogenic mechanism. Rosmarinic acid (RA) possesses beneficial properties, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
5
7
0
Order By: Relevance
“…Furthermore, rosmarinic acid inhibits gluconeogenesis and insulin resistance in rats [25]. In our previous in vitro study, we reported that rosmarinic acid effectively reduces oxLDL-induced cholesterol contents under high glucose (HG) conditions in macrophages by enhancing ABCA1 and ABCG1 expression [26]. In this study, we confirmed the protective effects of rosmarinic acid on hyperlipidemia in HFD-fed C57BL/6 mice and investigated the possible mechanism underlying the antihyperlipidemic effect of rosmarinic acid in vivo.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, rosmarinic acid inhibits gluconeogenesis and insulin resistance in rats [25]. In our previous in vitro study, we reported that rosmarinic acid effectively reduces oxLDL-induced cholesterol contents under high glucose (HG) conditions in macrophages by enhancing ABCA1 and ABCG1 expression [26]. In this study, we confirmed the protective effects of rosmarinic acid on hyperlipidemia in HFD-fed C57BL/6 mice and investigated the possible mechanism underlying the antihyperlipidemic effect of rosmarinic acid in vivo.…”
Section: Introductionsupporting
confidence: 73%
“…Some researchers have studied the effect of rosmarinic acid in animal model at various dose ranges between 2.5 and 200 mg/kg [23,[27][28][29][30]. Our previous in vitro study showed that rosmarinic acid effectively reduced oxLDL-induced cholesterol contents under HG conditions in macrophages at 50 and 100 µM [26]. Based on these reports, we investigated the protective effects of rosmarinic acid on hyperlipidemia in HFD-fed C57BL/6 mice at 50 mg/kg and 100 mg/kg.…”
Section: Rosmarinic Acid Reduces Body Weight and Blood Glucose In Hfd-fed Micementioning
confidence: 99%
“…It has been proven that the JAK2/STAT3 pathway upregulates the levels of ABCA1, ABCG1 and SR-BI and mediates cholesterol efflux in macrophages. 26 In this study, we found a reduction in ABCA1, found that NE appears to play a role in foam cell formation by preventing cholesterol efflux from macrophages by promoting ABCA1 degradation. 27 NPY, as a cotransmitter, is mainly found in postganglionic sympathetic neurons and is released simultaneously with norepinephrine (NE) in response to sympathetic stimulation.…”
Section: Npy Inhibited Abca1 Abcg1 and Sr-bi Expression Via The Jak2/...supporting
confidence: 52%
“…The health-promoting benefits of RA could be based on scavenging reactive oxidation species, decreasing nitric oxide production, lipid peroxidation, increasing high-density lipoprotein, decreasing low-density lipoprotein levels, and deranged hemolysis (Baba et al 2004 ; Guo et al 2020 ). Nyandwi et al ( 2021b ) has reported lipid-lowering effects of RA through modulation of reverse cholesterol transport-related proteins, thereby combating hyperlipidemia-based disorders. RA also increased macrophage cholesterol influx via regulation of ABCA1 transporter expression through JAK2/STAT3, JNK, and PKC-p38 and ABCA2 expression JAK2/STAT3, JNK, and PKC-ERK1/2/p38 (Nyandwi et al 2021a ).…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%